Comparative efficacy and safety of sunitinib vs sorafenib in renal cell carcinoma: A systematic review and meta-analysis. Issue 13 (March 2020) - Liu, Xiu-Lan; Xue, Hui-Ying; Chu, Qian; Liu, Jin-Yu; Li, Juan
Abstract : Abstract: To evaluate the safety and efficiency of sunitinib and sorafenib in the treatment of renal cell carcinoma (RCC). Databases were searched up till February 28, 2018. Two reviewers independently assessed trials for eligibility, quality, and extracted relevant data. Results are expressed as risk ratio (RR) or hazard ratio (HR) with 95% confidence intervals (CI). Six studies including 3112 patients were accessed. Sorafenib group exhibited higher median progression-free survival (mPFS) compared to sunitinib group (MD, −1.30; 95% CI, −2.56 to −0.03), especially in the first-line treatment (MD, −1.33; 95% CI, −2.61 to −0.04). However, sunitinib significantly reduced the risk of progression-free survival (PFS) compared to sorafenib (HR, 0.71; 95% CI, 0.6–0.82). Sunitinib also significantly reduced risk of overall survival (OS) compared to sorafenib (HR, 0.79; 95% CI, 0.65–0.92), while median OS was similar in both groups (MD, −0.48; 95% CI, −3.40–2.43). With regards to safety, the risk of rash (RR, 0.31, 95% CI, 0.12–0.79) was greater in sunitinib than sorafenib group, while the risk of decreased appetite (RR 2.10, 95% CI: 1.33–3.30) and dehydration (RR 2.73, 95% CI: 1.14–6.56) was smaller in contrast. Based on risk of PFS and OS, sunitinib was a better treatment option for RCC treatment while patients faced with severe skin reaction. And for those Asian patients classified under MSKCC moderate risk, whether in first or second-line treatment, had difficulty in feeding, sorafenib is a better choice for prolong mPFS. Abstract : Supplemental Digital Content is available in the text